Three‐year follow‐up of the use of a levonorgestrel‐releasing intrauterine system in hormone replacement therapy - Satu Suhonen; Teddy Holmström; Pekka Lähteenmäki (Acta Obstetricia et Gynecologica Scandinavica)
Background. The efficacy of a levonorgestrel‐releasing intrauterine system in opposing endometrial proliferation and in preventing bleeding was studied in peri‐ and postmenopausal women receiving estrogen replacement therapy. Methods. This was an open, non‐controlled follow‐up study of the use of a levonorgestrel‐releasing intrauterine system during continuous estrogen replacement therapy carried out by using oral, transdermal or subdermal estradiol. The efficacy of the progestin therapy was evaluated by transvaginal ultrasonography and by examination of endometrial biopsy samples taken 20 months (mean, range 17–22; first evaluation) and 34 months (mean, range 31–38 months; second evaluation) after insertion of the levonorgestrel‐releasing intrauterine system, and by studying patterns of bleeding. Twenty‐five women participated in the first evaluation, and 29 in the second. Results. Seventy‐six percent of the women were amenorrheic at the first evaluation, and 79% at the second evaluation. Others had spotting for 1–2 days monthly or less often. The mean time until amenorrhea was reached was 6 months (range 2–13 months) after insertion of the levonorgestrel‐releasing intrauterine system. The median endometrial thickness assessed by ultrasound was 2 mm at both evaluations. No signs of proliferation were observed in any of the endometrial samples. Conclusions. Local progestin delivery via a levonorgestrel‐releasing intrauterine system was effective in suppressing the endometrium and in eliminating bleeding in women receiving estrogen replacement therapy, and the intrauterine progestin therapy was also well accepted.